USING VOICE RECORDER TO IMPROVE STUDENTS’ SPEAKING SKILL AT SMP NEGERI 3 TONDANO - Ni Wayan Dessy Anggreni; Tini Mogea; Tirza Kumayas (Program Studi Pendidikan Bahasa Inggris, 2022)
Language is one of the abilities possessed by everyone to communicate with others. There are some students who have difficulty in speaking English. This happened because they feel that speaking English is a difficult thing, beside that they also feel confused when asked to speak 1 word in EnglishThe purpose of this research to find out whether using voice recorder can improve students speaking skill. This study was carried out on third grade students at SMP Negeri 3 Tondano during the academic year 2022/2023. A quantitative research approach was used in this pre-experimental study. There are 32 students in one class for the subject. The experiment was divided into three stages: pre-test, treatment, and post-test. The instrument of the study was the oral test. The datum was obtained by pre-test and post-test. Before giving the treatment, the writer administered the pre-test to find out student’s speaking skill at the beginning. The post test was conducted at the end after gave the treatment. The result showed that the average post-test score (4,12) was the higher of the pre-test score (2,5).